Koncert dla Przodowników Pracy w Porcie. (Gdańsk : [s.n.], 1948)
Afisz inf. o koncercie 3.09.1948 r.
Keywords: Polskie Radio. -- Regionalna Rozgłośnia w Gdańsku "Radio Gdańsk" -- 1945-1970 -- druki ulotne; Życie muzyczne -- Polska -- Gdańsk -- 1945-1970.; Gdańsk (Polska) -- 1945-1970 -- druki ulotne